Description of the third instar larva and pupa of Macraspis morio Burmeister, 1844 (Coleoptera: Scarabaeidae: Rutelinae) from Southern Brazil - Begha, Bruno Piotrovski; Santos, Mateus Henrique (Papéis Avulsos de Zoologia, 2020)
The third instar larva and pupa of Macraspis morio Burmeister, 1844 (Rutelinae: Rutelini: Anticheirina), collected in Paraná, Brazil, is described and illustrations and comments are given. The larva differs from other Macraspis larvae by the head with 6 posterofrontal setae and mandibles with a blunt second left incisor tooth. The pupa is similar to that of M. festiva Burmeister, 1844.